Executors Satisfaction Regarding Educational Process Developmental Projects and Programs in Oman from Teacher's perspective and How the Saudi Education Utilized the Omani Experience: Dhofar District Model - Al Osaimi, Noura Ahmed (Journal of Educational and Psychological Sciences, 2018)
The current study aimed to investigate the educational system in Oman at its various stages, also, recognize executor's satisfaction regarding educational process developmental projects and programs in Oman from teacher's perspective and how the Saudi education utilized the Omani experience. The researcher used the descriptive analytical methodology, and he implemented questionnaire. The number of sample members was (33) teachers in Dhofar Governorate of Oman. The results indicated that the majority of the sample strongly approve on the effectiveness of projects and programs in terms of planning, as their approval degree on the technical terms was a homogenous with their approval on the effectiveness of projects and programs in terms of planning, the results also indicated that the sample members agreed on the effectiveness of one of the educational projects and programs in the educational system in terms of educational aspects. The study recommended the use of Oman's experience in implementing the programs in the gulf countries, which included the implementation of the programs of life skills and the educated village, and the importance of issuing a guide to developmental programs and projects for each of the Arab gulf countries, in addition to expanding the exchange of experiences among gulf countries.
Keywords: education; educational programs; educational projects